Analysis on the application of FMEA in ‘instrument and equipment surface cleaning and disinfection’ in hospitals based on standardization and cleaning and disinfection information system management - Zheng, Jing; Wang, Ling; Fang, Yihai; Xu, Xuejun; Hu, Li (Frontiers in Public Health, 2024)
Purpose To analyze the application of ‘instrument and equipment surface cleaning and disinfection’ in hospitals based on standardization and the management of cleaning and disinfection information systems. Methods Employees and all cleaning and disinfected instruments and equipment from 56 inpatient departments in our hospital were selected as the subjects of observation. The period before the intervention (January 2023) was designated as the control group, while the period after the intervention (July 2023) was designated as the study group. In the control group, the instruments and equipment under routine management were disinfected. The research team applied the Failure Mode and Effects Analysis (FMEA) method to clean and disinfect the surfaces of instruments and equipment on the basis of standardization and cleaning and disinfection information system management. Employees’ theoretical knowledge points and operational skill scores before and after the intervention were compared and evaluated. The changes in the risk priority coefficient (RPN) values of high-risk factors were analyzed. Fifty-six clinical medical staff from 56 inpatient departments in the hospital were selected to evaluate the clinical satisfaction of the cleaning and disinfection management of instruments and equipment before and after the intervention, and the clinical satisfaction of the two groups was compared. Results The scores of theoretical knowledge and operational skills of the staff in the research group were significantly higher than those in the control group. The passing rates of theoretical knowledge and operational skills in the control group and the research group were 44.64 and 94.64% respectively, and 55.36 and 96.43%, respectively. The qualified rate of theoretical knowledge and operational skills of staff in the study group was significantly higher than that in the control group (p < 0.05). The RPN scores of medical personnel, environment, system and system guarantee factors in the control group were 80, 80, 80, and 100, respectively. The RPN scores of medical personnel factors, environmental factors, system factors and system guarantee factors in the research group were 6, 24, 24, and 36, respectively. Conclusion Through standardization and cleaning and disinfection information system management, the theoretical knowledge and technical operation capabilities of cleaning can be effectively improved.